2022
DOI: 10.1553/populationyearbook2022.dat.3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid changes in birth counts in Brazilian major cities during the COVID-19 pandemic

Abstract: Since the beginning of the coronavirus pandemic, Brazil has been among the countries that have been heavily affected by this novel disease. From March 2020 onwards, records of deaths in Brazil increased as the number of COVID-19 infections skyrocketed. Consequently, many studies have tried to explain how this illness has affected the overall number of deaths since the start of the pandemic, and have examined the question of whether mortality related to COVID-19 has led to reductions in life expectancy. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Second, aggregate‐level changes in births, conceptions, and pregnancy terminations may not reflect the impacts of the pandemic due to the existence of temporal and seasonability effects. This observation is in line with recent studies on fertility responses to the pandemic, which consider these confounding factors (Lima, Soares, and Silva 2022; Silverio‐Murillo et al. 2023).…”
Section: Discussionsupporting
confidence: 89%
“…Second, aggregate‐level changes in births, conceptions, and pregnancy terminations may not reflect the impacts of the pandemic due to the existence of temporal and seasonability effects. This observation is in line with recent studies on fertility responses to the pandemic, which consider these confounding factors (Lima, Soares, and Silva 2022; Silverio‐Murillo et al. 2023).…”
Section: Discussionsupporting
confidence: 89%
“…However, the existing evidence on the impacts of the pandemic on fertility in low-and middle-income countries is much more sparse due to the lack of timely data. Lima et al (2022) observed a large decline in the number of births in some Brazilian cities in late 2020 and early 2021 compared to previous years. Dasgupta et al (2020) prospectively considered a scenario of the potential impact of the COVID-19 pandemic on contraceptive use in which the proportion of the need for family planning satisfied by modern methods is expected to decrease particularly sharply in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 82%
“…For most of the highly developed countries, these data confirmed the expected baby bust associated with the first wave of the pandemic and the lockdowns. Sharp falls in the number of births were also reported in middle-income countries of Latin America (e.g., Lima et al 2022, UN 2021 and in China (Zhang andLi 2021, UN 2021). However, analyzes covering longer period of the pandemic increasingly revealed a more differentiated picture, with birth trends varying substantially over time and across countries.…”
Section: Introductionmentioning
confidence: 92%